Pengaruh dan Pencegahan Sleep Apnea dalam Perspektif Hadis: Studi di Program Studi Ilmu Hadis UIN Sumatera Utara - Anggraini, Diana; Hasibuan, Sahdin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
This study aims to explore the influence of knowledge about sleep apnea and the application of hadith teachings in preventing sleep disorders among students of the Hadith Studies Program at UIN Sumatera Utara. Employing a quantitative approach with a cross-sectional design, the study involved 25 purposively selected respondents. Data were collected through a questionnaire covering three main aspects: knowledge of sleep apnea, sleep quality (measured using the Pittsburgh Sleep Quality Index/PSQI), and perspectives and practices related to sleeping habits based on hadith. The results revealed that 52% of respondents had low knowledge of sleep apnea, although 72% reported good sleep quality. Statistical analysis showed a significant relationship between knowledge of sleep apnea and the application of hadith teachings (p-value 0.036), as well as between sleep quality and hadith practice (p-value 0.022). These findings indicate that students with better knowledge and sleep quality tend to consistently practice the sleep-related sunnah of Prophet Muhammad ﷺ, which medically may reduce the risk of sleep apnea. This study highlights the importance of education on sleep apnea and the application of prophetic traditions as preventive measures to maintain sleep quality and overall health.